Analisis Stakeholders pada Pelatihan Manajemen Strategis dengan Metode Daring di Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta - Yurianto Yurianto (Universitas Indraprasta PGRI, 2021)
The level of quality of an online learning system is highly dependent on various factors. The main objective of this study is to analyze the role of each stakeholder in strategic management training. The location of research activities is carried out at BPSDM DKI Jakarta Province. In collecting data, using the purposive sampling technique. Based on the results of stakeholder identification, it is known that there are 15 (fifteen) stakeholders involved in strategic management training. Based on the analysis, it was found that training) is needed by Civil Servants (PNS) to improve competence. The stakeholders who are the key to implementing strategic management training include BPSDM, BKD, BPKD, BAPPEDA. In order for training to be optimal, it has to be collaborated among stakeholders professionally dan proportionally. Furthermore, collaboration is effective and efficient if it is supported by balanced and respectful communication, coordination, and cooperation